Motivating people for improved performance (Boston, MA, 2005)
Managers are under increasing pressure to deliver better results faster than the competition. But meeting today's tough challenges requires complete mastery of a full array of management skills, from communicating and coaching to public speaking and managing people. The Results-Driven Manager series is designed to help time-pressed managers hone and polish the skills they need most. Concise, action-oriented, and packed with invaluable strategies and tools, these timely guides will help managers improve their job performance today-and give them the edge they need to become the leaders of tomorrow.
Keywords: Employee motivation,Supervision of employees,Performance; Management